1998
DOI: 10.1103/physrevlett.81.4476
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Phase Diagram of SuperconductingU1xThx

Abstract: Low-temperature specific-heat and thermal-expansion measurements on a single crystal of the heavyfermion superconductor UBe 13 reveal an anomaly in the superconducting state. The evolution of this feature is studied as a function of Th doping on several U 12x Th x Be 13 polycrystals (x # 0.03), giving rise to a new "line of anomalies," T L ͑x͒, in the T -x diagram. The anomaly at T L ͑x͒ marks the precursor of the lower of the two phase transitions at x . x cr ഠ 0.019. Implications for the interpretation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 20 publications
5
79
1
Order By: Relevance
“…14 At nearly the same field ∼ 4 T, the specific heat and thermal expansion measurements 9,10 have suggested that there is an anomaly at B * below B c2 , as mentioned in Introduction. Ac-susceptibility also shows an anomaly at ∼ 4 T for T ∼ 0.25 K. 15 All works may suggest the same anomaly because these anomalies have been observed in nealy same field range: B ≤ 4.5 T in the superconducting phase diagram.…”
Section: J P H Y S S O C J P N D O W N L O a D E D F R O M J mentioning
confidence: 99%
See 1 more Smart Citation
“…14 At nearly the same field ∼ 4 T, the specific heat and thermal expansion measurements 9,10 have suggested that there is an anomaly at B * below B c2 , as mentioned in Introduction. Ac-susceptibility also shows an anomaly at ∼ 4 T for T ∼ 0.25 K. 15 All works may suggest the same anomaly because these anomalies have been observed in nealy same field range: B ≤ 4.5 T in the superconducting phase diagram.…”
Section: J P H Y S S O C J P N D O W N L O a D E D F R O M J mentioning
confidence: 99%
“…It has been proposed that this anomaly is a precursor of another phase transition observed in the U 1−x Th x Be 13 system at T c2 , 8 because it seems that T L (x) smoothly merges into * E-mail address: yusei@phys.sci.hokudai.ac.jp T c2 (x) on a T -x phase diagram. 9,10 In order to obtain further information about this unusual superconductivity of UBe 13 , we have performed lowtemperature specific heat and static dc magnetization measurements for the superconducting state of UBe 13 using a high-quality single crystal. In the present paper, we report the superconducting phase diagram along [110] axis by our specific heat and dc magnetization measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This anomaly cannot be seen in the temperature dependence of the specific heat at zero field, but in field, the isothermal specific heat curves C(B) show a broad anomaly at a corresponding field called B * (T L ). 17) On the other hand, an L-type UBe 13 has a lower T c of ∼ 0.75 K, and it exhibits an obvious anomaly named T A below T c in the temperature dependence of the zero-field specific heat. It has been found that T A corresponds to the thermal-expansion anomaly T L .…”
mentioning
confidence: 99%
“…The common feature of the parent compounds [8,9,10,11,12,13,14] is a distinct, moderately high temperature (above ∼ 100 K), coupled, structural/antiferromagnetic phase transition that generally is argued to be of the first order. Thermal expansion is often claimed to be uniquely sensitive to just such magnetic, structural and superconducting transitions [15]. For example, in Co-doped BaFe 2 As 2 , anisotropic thermal expansion measurements [16,17,18] have been instrumental in inferring unusually large, anisotropic, uniaxial pressure derivatives of superconducting transition temperature.…”
mentioning
confidence: 99%